Analyses of rainfall trends in the Nile River Basin - Onyutha, Charles; Tabari, Hossein; Taye, Meron T.; Nyandwaro, Gilbert N.; Willems, Patrick (Journal of hydro-environment research, 2016)
Trends in rainfall at 39 locations of the Nile River Basin (NRB) in Africa were analyzed. Comparison was made between rainfall trend results from the long-term data and those of short-term series selected over different time periods. The bias on trend results from series of short-term records was quantified. Homogeneity test was conducted to assess the coherence of the trend directions on a regional basis. Based on an assumed population (for simplicity) of rainfall data time periods in the range 75–100 years, bias in the short-term trend analysis was noted to reduce by about 10% for every 10% increase in record length. Under some conditions if respected, it was possible to derive trends at stations with short records based on those at nearby stations with longer term records but in the same region. Using the same data record length and uniform time period at all the selected stations, an improved regional coherence of rainfall trend results was obtained. In the equatorial region, trend in annual rainfall was found mainly positive and significant at level α = 5% in 4 of the 7 stations. Collectively for Sudan, Ethiopia and Egypt, trends in the annual rainfall were mostly negative and significant at α = 5% in 69% of the 32 stations. Heterogeneity in the trend directions for the entire NRB was confirmed at α = 1% in 13% of the 39 stations. These findings are vital for water and agricultural management practices. © 2015 International Association for Hydro-environment Engineering and Research, Asia Pacific Division. Published by Elsevier B.V. All rights reserved.
Keywords: Trend analysis; Trend homogeneity; Sub-trend identification; Mann–Kendall test; Rainfall; Nile River Basin